Violência contra criança e adolescente: levantamento do conhecimento do graduando em odontologia acerca da conduta a ser adotada frente à casos de suspeita de violência - Cunha, Isadora Eugenia Eurídice Alvarez da [UNESP] (Universidade Estadual Paulista (Unesp), 2024)
Objetivo: levantar, junto a graduandos de Odontologia, o conhecimento sobre a responsabilidade ética e conduta a ser adotada ante a suspeita de violência contra criança e adolescente. Material e Métodos: Para o desenvolvimento desta pesquisa exploratória, uma amostra de 150 graduandos dos últimos anos de Odontologia de faculdades, públicas e privadas do interior do estado de São Paulo foram convidados a responder a um questionário estruturado autoaplicável, após anuir ao Termo de Consentimento Livre e Esclarecido. Resultados: A pesquisa contou com 75 participantes regularmente matriculados no quarto ou quinto ano de Odontologia de faculdades do interior do Estado de São Paulo, que responderam 19 questões. Conclusão: conclui-se conhecimento satisfatório por parte dos graduandos quanto à conduta, contudo, estes possuem certas inseguranças relacionadas ao tema, além disso demonstram interesse em saber mais sobre o tema.

Objective: The purpose of this research is to raise knowledge about ethical responsibility and conduct [to be adopted] in the face of suspected violence against children and adolescents. Material and Methods: For the development of this exploratory research, a sample of 150 undergraduate students of the last years of Dentistry from public and private schools in the interior of the state of São Paulo] were invited to answer a self-administered structured questionnaire, after agreeing to the Free and Informed Consent Form. Results: The research had 75 participants regularly enrolled in the fourth or fifth year of Dentistry at schools in the interior of the State of São Paulo, who answered 19 questions. Conclusion: It is concluded that the undergraduates have satisfactory knowledge about the conduct, however, they have certain insecurities related to the theme, in addition to showing interest in knowing more about the subject.
Violence against children and adolescents: survey of the knowledge of the undergraduate student in dentistry about the conduct to be adopted in cases of suspected violence
Keywords: Defesa da riança e do adolescente; Maus-tratos infantis; Odontologia; Odontologia Legal; Odontopediatria; Child advocacy; Child abuse; Dentistry; Forensic dentistry; Pediatric dentistry